Evidence for adult age-invariance in associative false recognition. Issue 2 (7th February 2020) - Pansuwan, T.; Breuer, F.; Gazder, T.; Lau, Z.; Cueva, S.; Swanson, L.; Taylor, M.; Wilson, M.; Morcom, A. M.
ABSTRACT: Older people are more prone to memory distortions and errors than young people, but do not always show greater false recognition in the Deese–Roediger–McDermott (DRM) task. We report two preregistered experiments investigating whether recent findings of age-invariant false recognition extend to designs in which studied items are blocked. According to (Tun, P. A., Wingfield, A., Rosen, M. J., & Blanchard, L. (1998). Response latencies for false memories: Gist-based processes in normal aging. Psychology and Aging, 13(2), 230–241.), age effects on false recognition in the DRM task are due to a greater reliance on gist processing which is enhanced under blocked study conditions. Experiment 1 assessed false recognition in an online variant of the DRM task where words were presented visually, with incidental encoding. The results showed Bayesian evidence against greater false recognition by older adults, whether lures were semantically associated with studied lists, or perceptually related (presented in the same distinctive font as studied lists) or both. Experiment 2 used a typical DRM procedure with auditory lists and intentional encoding, closely reproducing (Tun, P. A., Wingfield, A., Rosen, M. J., & Blanchard, L. (1998). Response latencies for false memories: Gist-based processes in normal aging. Psychology and Aging, 13(2), 230–241.) Experiment 2 but omitting an initial test of recall. The results showed evidence against an age-related increase in critical lure false recognition under these conditions. Together, the data suggest that older people do not make more associative memory errors in recognition tests than young people.